2013
DOI: 10.1556/eujmi.3.2013.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of easy-to-perform procedures to reduce bacterial colonization withStreptococcus mutansandStaphylococcus aureuson toothbrushes

Abstract: It is well known that dental caries and periodontitis are the consequence of bacterial colonization and biofilm formation on the enamel surface. The continuous presence of bacterial biofilms on the tooth surface results in demineralization of the tooth enamel and induces an inflammatory reaction of the surrounding gums (gingivitis). The retention and survival of microorganisms on toothbrushes pose a threat of recontamination especially for certain patients at risk for systemic infections originating from the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…Bacteria harboring pR ST98 developed slimy and viscous pellicles, while pR ST98 -free bacteria formed loose and less coherent BFs [13] . Tomography and three-dimensional reconstruction by CLSM showed that BFs in S. typhi ST 8 and ST 8 -c-pR ST98 were developed with 43.23 µm and 47.62 µm thicknesses, respectively, which were much thicker than that in ST 8 -ΔpR ST98 with a thickness of 21.74 µm; S. Typhimurium harboring pR ST98 was a stronger BF developer (χ3337: 24.22 µm vs χ3337/pR ST98 : 44.33 µm; χ3337 lux : 25.89 µm vs χ3337 lux /pR ST98 : 40.30 µm); E. coli K 12 W 1485 produced a BF of 9.1 µm in thickness, while the BF developed by E. coli K 12 W 1485 /pR ST98 had a thickness of 45.06 µm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria harboring pR ST98 developed slimy and viscous pellicles, while pR ST98 -free bacteria formed loose and less coherent BFs [13] . Tomography and three-dimensional reconstruction by CLSM showed that BFs in S. typhi ST 8 and ST 8 -c-pR ST98 were developed with 43.23 µm and 47.62 µm thicknesses, respectively, which were much thicker than that in ST 8 -ΔpR ST98 with a thickness of 21.74 µm; S. Typhimurium harboring pR ST98 was a stronger BF developer (χ3337: 24.22 µm vs χ3337/pR ST98 : 44.33 µm; χ3337 lux : 25.89 µm vs χ3337 lux /pR ST98 : 40.30 µm); E. coli K 12 W 1485 produced a BF of 9.1 µm in thickness, while the BF developed by E. coli K 12 W 1485 /pR ST98 had a thickness of 45.06 µm.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance against multiple antibiotics is greatly increased when Salmonella is enclosed in a BF [12] , which makes BF-related diseases more difficult to treat or cure. The persistence of bacterial BFs on the surface of teeth damages the tooth enamel and induces an inflammatory reaction in the surrounding gums [13] . S. Typhi BFs formed on the gallbladder were reported to be associated with the occurrence of liver cancer [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Citrobacter sp., Serratia sp., Candida albicans, Escherichia coli and Bacillus subtilis. [3,[12][13][14] Several different methods are used to reduce microbes in toothbrush such as soaking, toothbrush in alcohol or disinfectant solution, ultraviolet radiation. [5,7,13] However, research results show that toothbrushes are placed in closed containers and exposed to contaminated surfaces resulting in higher bacterial counts than those left open.…”
Section: Discussionmentioning
confidence: 99%
“…A escova representa um recurso simples, eficaz, com alcance coletivo e boa repercussão social, sendo indispensável para a manutenção da saúde bucal. Apesar da importância da escova, esta pode ser um potencial transmissor de doenças, pois pode tornar-se contaminada por microrganismos vindos do biofilme oral, do meio a que está exposta ou de ambos [8,17,21].…”
Section: Introductionunclassified